2013
DOI: 10.1186/1471-2458-13-565
|View full text |Cite
|
Sign up to set email alerts
|

Health coping strategies of the people vulnerable to climate change in a resource-poor rural setting in Bangladesh

Abstract: BackgroundAmong the many challenges faced by the people of Bangladesh, the effects of climate change are discernibly threatening, impacting on human settlement, agricultural production, economic development, and human health. Bangladesh is a low-income country with limited resources; its vulnerability to climate change has influenced individuals to seek out health coping strategies. The objectives of the study were to explore the different strategies/measures people employ to cope with climate sensitive diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
(31 reference statements)
3
39
0
Order By: Relevance
“…The findings of this paper are consistent with those of other research work on health, ecological, economic, and social network impacts in coastal settings in Bangladesh [26,76,79,81,82]. The present paper identified the consequential occurrence of different orders of impacts on six surveyed agricultural communities.…”
Section: Social Network Securitysupporting
confidence: 89%
“…The findings of this paper are consistent with those of other research work on health, ecological, economic, and social network impacts in coastal settings in Bangladesh [26,76,79,81,82]. The present paper identified the consequential occurrence of different orders of impacts on six surveyed agricultural communities.…”
Section: Social Network Securitysupporting
confidence: 89%
“…There is no especial reason why they should have: Bangladesh's history, from long before independence, involves interconnecting migration, poverty, livelihoods, and calamity from environmental hazards and from conflict, amongst other factors. Migration, even when principally forced rather than voluntary, in the respondents' views, is used to cope with and adapt to a wide variety of circumstances including but not limited to climatic influences, a viewpoint corroborated by the literature on Bangladesh [27,39,41,[63][64][65]. The literature beyond Bangladesh also aligns with this view [1][2][3]5,8,25,26] including for locations such as small islands [9,[22][23][24] and the Sahel [19][20][21].…”
Section: Migration As Climate Change Adaptation?mentioning
confidence: 80%
“…Bangladesh is frequently labeled as being amongst the most vulnerable countries to climate change [27][28][29][30][31]. One consequence could be that about 20 per cent of the entire country eventually becomes submerged due to sea-level rise and subsequent erosion, with the loss of coastal land projected to reach up to 3% by the 2030s, 6% by the 2050s, and 13% by 2080 [32].…”
Section: Environmental Change and Migration In Bangladeshmentioning
confidence: 99%
“…Research projects that, Bangladesh will be one of the worst victims of climate change A number of studies indicated that climate change has 1 affecting general health of the population in Bangladesh . Climate change increases the incidences of water borne and air borne diseases and changes in the climatic condition is suitable for bacteria, parasites and disease vectors to breed 4 very rapidly . The magnitude of malaria, dengue, childhood diarrhoea and pneumonia is very high among the affect 3 communities in Bangladesh.…”
mentioning
confidence: 99%
“…The magnitude of malaria, dengue, childhood diarrhoea and pneumonia is very high among the affect 3 communities in Bangladesh. Climate change is also responsible for severe health problems like dehydration, malnutrition and heat related morbidity among the children 4 and elderly population . In Bangladesh, so far number of health problems like colds, coughs, fevers, dysentery, headaches, skin diseases, burning sensations, conjunctivitis, jaundice, Hepatitis-B, skin burns/blistering, asthma, typhoid, pox, weight loss, rheumatism/aching, pneumonia are 4 associated with extreme weather events .…”
mentioning
confidence: 99%